Analysis of Konya Alaeddin Mosque Seljuk Period Inscriptions in Terms of Calligraphy - Betül Erikoğlu (Art-Sanat)
Alaeddin Mosque is located on Alaeddin Hill in the center of Konya, the capital of the Anatolian Seljuk State. The stages of Alaeddin Mosque, one of the important structures of this period, from its construction to its completion are quite long. The construction of the mosque was started by Mesud I. The sultans who came after Mesud I also made additions to the mosque in the process. Kilijarslan II’s grandson Kaykaus I ordered the construction of the current middle part and the western wing of the mosque, but when he passed away, the remaining parts of the mosque were completed by his brother Ala al-Din Kayqubad I. There are various inscriptions from the Seljuk period on the building. In this study six construction inscriptions, two on the western wall of the mosque and four on the northern wall, pulpit and mihrab inscriptions, trustee and master inscriptions, tile inscriptions, inscriptions containing the Surah al-Fath and the word Tawhid were evaluated in terms of calligraphy. These inscriptions, written using various materials such as marble, wood and tile, are important in terms of giving an idea about the writing style of the Seljuk Period, such as the design of the text, the way the letters are written, their sizes, directions and the signs used.